Doxazosin induces apoptosis of cells expressing hERG K(+) channels - Thomas, Dierk (2007)
The antihypertensive drug doxazosin has been associated with an increased risk for congestive heart failure and cardiomyocyte apoptosis. Human ether-a-go-go-related gene (hERG) K(+) channels, previously shown to be blocked by doxazosin at therapeutically relevant concentrations, represent plasma membrane receptors for the antihypertensive drug. To elucidate the molecular basis for doxazosin-associated pro-apoptotic effects, cell death was studied in human embryonic kidney cells using three independent apoptosis assays. Doxazosin specifically induced apoptosis in hERG-expressing HEK cells, while untransfected control groups were insensitive to treatment with the antihypertensive agent. An unexpected biological mechanism has emerged: binding of doxazosin to its novel membrane receptor, hERG, triggers apoptosis, possibly representing a broader pathophysiological mechanism in drug-induced heart failure.